Kuwait : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The Statistical Appendix of Kuwait discusses the basic social and demographic indicators, selected economic indicators, GDP, balance of payments, gross domestic expenditure, LPG and oil production, disposal, and prices, consumer price index, wholesale price index, industrial output, agricultural and fisheries production, population and employment, government revenue, import and export, bank credit and interest rates, monetary accounts and monetary survey, and summary of government finance for the period 2001-07.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet